Incremental semantic restriction and subjectivity-based adjective ordering - Scontras, Gregory; Bar-Sever, Galia; Kachakeche, Zeinab; Rosales Jr., Cesar Manuel; Samonte, Suttera (Proceedings of Sinn und Bedeutung, 2020)
Adjective ordering preferences (e.g., big blue box vs. blue big box) are robustly attested in many unrelated languages (Dixon, 1982). Scontras et al. (2017) showed that adjective subjectivity is a robust predictor of ordering preferences in English: less subjective adjectives occur closer to the modified noun. In a follow-up to this finding, several authors have claimed that pressures from successful reference resolution and the hierarchical structure of modification explain subjectivity-based ordering preferences (Simonic?, 2018; Franke et al., 2019; Scon- tras et al., 2019). In cases of restrictive modification, adjectives that compose with the nominal later will classify a smaller set of potential referents (e.g., the set of boxes vs. the set of blue boxes). To avoid alignment errors where a listener might mis-characterize the intended referent, speakers introduce the more error-prone (i.e., more subjective) adjectives later in the hierarchical construction of nominal structure; the structure linearizes such that subjectivity decreases the closer you get to the modified noun. The current study explores the predictions of this reference-resolution story by examining adjective ordering cross-linguistically: when adjectives incrementally restrict a nominal denotation, there should be pressure toward subjectivity- based orderings, but, in the absence of incremental restriction, such pressures should not obtain.